Organophosphates and monocyte esterase deficiency. - McClean, E (1995)
AIMS--To examine the possibility that monocyte esterase deficiency (MED) could be caused by exposure to organophosphates. METHODS--Pseudocholinesterase, paraoxonase and arylesterase activities were measured in the serum and acetylcholinesterase activity was measured in the red cells of a group of monocyte esterase deficient subjects and compared with the enzyme activities of a control group of monocyte esterase positive subjects. RESULTS--No significant difference was found between the enzyme activities of the monocyte esterase deficient group and the control group for any of the esterases investigated. CONCLUSION--Current or recent exposure to organophosphorus is not the cause of MED.